Kinetic and metabolic studies in HPRT deficiency - Steyn, Lafras Marais (Division of Chemical Pathology, 2018)
The patient (T.K.), was first diagnosed as having a partial hypoxanthine-guanine phosphoribosyltransferase deficiency in 1978 when he was 20 years old. At presentation, he complained of a colicky loin-pain which radiated into his groin, and that he had had dark urine for a month. He was shown to have haematuria and urate crystalluria, and had a serum urate of 0.8mmol/l (reference range 0.12-0.5mmol/l). The diagnosis was confirmed by demonstrating a haemolysate hypoxanthine-guanine phosphoribosyltransferase activity of 550μU/mg Hb (reference range 1680-2480μU/mg Hb). Studies to determine whether the low hypoxanthine-guanine phosphoribosyltransferase activity was caused by an altered Kₘ of the enzyme for one of its substrates, showed that there was substrate inhibition of the enzyme activity by hypoxanthine. This thesis examines the patient and the variant HPRT at three levels. Firstly, a detailed and comprehensive study of the kinetic properties of the variant enzyme was made. The novel feature of the kinetics is the presence of substrate inhibition by the purine bases, with a true Kᵢ value for hypoxanthine of 80± 20μM, and a normal value for the true Kₘ. The pattern of substrate inhibition is characteristic of that associated with the formation of a dead-end complex and double inhibition experiments indicate that the form of this complex is enzyme-hypoxanthine-PPi. These unusual kinetic properties provided an opportunity to study the order of substrate binding in a way not possible for the normal enzyme and showed an ordered sequential reaction mechanism. Some limited protein-structural studies were performed and showed an altered electrophoretic mobility for the variant enzyme in non-denaturing gels. Secondly, the purine metabolic pathways in cultured cells, derived from T.K., from a patient with the Lesch-Nyhan syndrome, and from normal individuals, were studied. The cells were labelled with precursors of the de novo or of the salvage pathways, usually in the presence of a reference label, and sometimes in the presence of inhibitors of the various steps in the purine metabolic pathways. Hypoxanthine salvage was about 10% of that of control cultures. The growth of cells in a variety of selective media was also studied. Thirdly, as physician in charge of T.K., I could monitor the progress of his hyperuricaemia and observe the effects of therapy throughout the duration of this project.